1998
DOI: 10.1007/s002689900351
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Cholecystectomy for Cholelithiasis during Infancy and Childhood: Cost Analysis and Review of Current Indications

Abstract: Eleven consecutive laparoscopic cholecystectomies (LCs) were performed between January 1994 and June 1996 compared with seven open cholecystectomies (OCs) performed previously at King Khalid University Hospital. The comparison included surgical, clinical, and economic factors, together with a review of the literature. In the laparoscopic group the main indication for cholecystectomy was symptomatic gallstones. Other indications include mucocele of the gallbladder and chronic cholecystitis. A total of eight chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 22 publications
(12 reference statements)
2
18
0
1
Order By: Relevance
“…Therefore, laparoscopic cholecystectomy is safe and effi- Kim et al [5] Newman et al [6] Jawad et al [7] Present study cacious in children, and it compares favorably with traditional open cholecystectomy in the pediatric age group.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, laparoscopic cholecystectomy is safe and effi- Kim et al [5] Newman et al [6] Jawad et al [7] Present study cacious in children, and it compares favorably with traditional open cholecystectomy in the pediatric age group.…”
Section: Discussionmentioning
confidence: 99%
“…Though there was an increased incidence in intra-abdominal surgical procedures (20%) compared to extracavitary procedures, no difference was observed whether the procedure was open or laparoscopic. Jawad et al 20 compared open ( n = 7) and laparoscopic cholecystectomy ( n = 11) and found reduced postoperative analgesic requirement and a reduced hospital stay in the latter group.…”
Section: Laparoscopic Cholecystectomymentioning
confidence: 99%
“…The initial series were simply observational in small groups of patients [14][15][16][17] or small groups compared with historical controls. [18][19][20] More recently, series of more than 100 children have been reported 21,22 albeit often from combined centres. All series show that LC is safe with a low risk of complications and probably reduces hospital stay.…”
Section: Laparoscopic Cholecystectomymentioning
confidence: 99%
“…The benefits of LC over open cholecystectomy have been well established for paediatric cohorts, reducing costs, post-operative hospitalisation, complications, and analgesia use [12] [13]. As with adults, the role of OTC has now come into question, bringing with it both advocacy and opposition.…”
Section: Discussionmentioning
confidence: 99%
“…The LC approach developed for adult surgery has now been well adopted by paediatric surgeons in the UK, with retrospective studies strongly advocating its use over open cholecystectomy [8][9][10][11][12][13]. LC is now chosen to minimise use of analgesics, reduce complications and to improve cosmesis [1] [9].…”
Section: Introductionmentioning
confidence: 99%